DITHYMOQUINONE DAN SENYAWA TURUNANNYA SEBAGAI KANDIDAT INHIBITOR PROTEIN NUKLEOKAPSID SIN NOMBRE VIRUS: STUDI IN SILICO - Muhammad Darryl Aghzuwwan Fiddianova; Ahmad Mukafi Mazidan; I Gusti Agung Setiawan; Nailah Putri Sisfani; Nisrina Nazihah Azaly; Nisrina Khairunnisa; Alfiyatul Khoiriyah; Arjuna Satrio Narendro Nutra Amputro; Irfan Indradinata Putra; Muhammad Bilal Akira; Imam Siswanto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Hantavirus infection remains a global health problem due to its high mortality rate and the lack of specific antiviral therapies. Sin Nombre Virus (SNV) is one of the most pathogenic hantavirus species, causing Hantavirus Cardiopulmonary Syndrome (HCPS) characterized by severe respiratory failure and high fatality rates. The nucleocapsid protein (NP) plays a critical role in the viral life cycle, making it a potential target for inhibitor development. This study aimed to evaluate the potential of dithymoquinone (DTQ) and ten of its derivatives as inhibitors of SNV nucleocapsid protein through an in silico approach. Molecular docking analysis was employed to predict binding affinity and molecular interaction patterns between ligands and the target protein (PDB ID: 5E05). The results showed that DTQ10 (with -NH-C₆H₄-COOH substituent) exhibited the best total grid score (-55.14 kcal/mol), supported by its larger molecular size and higher molecular weight, which enhance van der Waals interactions. Meanwhile, DTQ08 (with -NH-C₆H₅ substituent) demonstrated the best grid electrostatic (-5.61 kcal/mol) with a competitive total grid score (-49.96 kcal/mol), making it a superior candidate due to its strong polar interaction stability. These findings suggest that DTQ derivatives, particularly DTQ08 and DTQ10, have promising potential as inhibitors against the nucleocapsid protein of Sin Nombre Virus and warrant further investigation through in vitro and in vivo studies.